Kewajiban Mempekerjakan Penyandang Disabilitas Menurut Undang-Undang Nomor 8 Tahun 2016 Pada Perusahaan Swasta - Ade Ansah Muhamad Fauzi; Muhammad Yasir (JOURNAL of LEGAL RESEARCH, 2019)
AbstractPrivate companies have the responsibility to employ persons with disabilities, as stipulated in Article 53 of Law Number 8 of 2016 that private companies are required to employ 1% of workers with disabilities out of the total number of workers. This responsibility is not limited to only employing people with disabilities, but there are other obligations that must be done by the company, in order to provide decent and decent work for persons with disabilities. These obligations include providing job security, promoting promotions and providing accessibility to persons with disabilities.Keywords: Responsibility, Company, Persons with Disabilities